The Role of Public Relations in Improving Information Services at the Regional Office of the Ministry of Law and Human Rights, South Sulawesi - Niswaty, Risma; Aswita, Andi; Akib, Haedar (Pinisi Journal of Education and Management, 2023)
The role of Public Relations in improving information services at the Regional Office of the Ministry of Law and Human Rights, South Sulawesi. This research aims to determine the role of public relations in improving information services at the Regional Office of the Ministry of Law and Human Rights, South Sulawesi. This type of research is descriptive research using qualitative methods and approaches to determine the role of Public Relations in Improving Information Services at the Regional Office of the Ministry of Law and Human Rights, South Sulawesi. The number of informants in this research was 5 people, namely one head of the public relations sub-division and 4 informants who were the First Expert Public Relations Officers and young public relations officers. The data collection techniques used are the interview method and documentation method. The data analysis techniques used by researchers are data collection techniques, data condensation, data presentation, and conclusions. The results of this research show that the role of Public Relations in improving information services in the Regional Offices of the Ministry of Law and Human Rights can be said to "play a role" in improving information services, this is indicated by the research results on each indicator, namely: Expert Advisor, Communication Facilitator, Problem Solving Process Facilitator, and Communication Engineering. The role of public relations in improving information services at the Regional Office of the Ministry of Law and Human Rights, South Sulawesi, needs to be maintained while still paying attention to several other factors that can influence improving information services. Looking at the four roles of public relations in significantly improving information services at the Office of the Ministry of Law and Human Rights, South Sulawesi, the role is as a problem-solving process facilitator, communication facilitator, and communication technician)